Severe Parechovirus 3 Infections in Young Infants—Kansas and Missouri, 2014. (29th March 2017) - Midgley, Claire M; Jackson, Mary Anne; Selvarangan, Rangaraj; Franklin, Patrick; Holzschuh, Elizabeth L; Lloyd, Jennifer; Scaletta, Joseph; Straily, Anne; Tubach, Sheri; Willingham, Ashley; Nix, W Allan; Oberste, M Steven; et al.
Abstract : We describe here severe parechovirus 3 infection in neonates, including neurologic illness and seizures. Younger infants (as young as 5 days) were more likely than older infants to require intensive care Abstract: Background: Infection with parechovirus type 3 (PeV3) can cause severe neurologic and sepsis-like illness in young infants; clinical and epidemiologic descriptions have been limited. We aimed to characterize PeV3 illness and explore risk factors for acquisition in a cluster of neonatal cases at Children's Mercy Hospital in Kansas City, Missouri. Methods: Cerebrospinal fluid specimens were obtained from infants aged <180 days who were hospitalized with sepsis-like illness or meningitis between June 1 and November 1, 2014. PeV-positive specimens were sequenced at the Centers for Disease Control and Prevention. We reviewed the medical and birth charts of the infants and performed face-to-face parent interviews. We analyzed characteristics according to infant age and intensive care admission status. Results: We identified 35 cases of PeV infection in infants aged 5 to 56 days. Seven infants required intensive care (median age, 11 days vs 27 days among those who did not require intensive care; P = .0044). Six of these 7 infants had neurologic manifestations consistent with seizures, and all 6 of them were treated with acyclovir but subsequently tested negative for herpes simplex virus. Virus sequences formed 2 lineages, both of which were associated with severe illness. Half of the infants were reported to have household contacts who were ill during the week before onset. Infants aged ≤7 days at onset were more likely to have been delivered at the same hospital. Conclusions: PeV3 can cause severe neurologic illness in neonates, and younger infants are more likely to require intensive care. PeV3 should be considered along with herpes simplex virus and other pathogens when evaluating young infants with sepsis-like illness or meningitis. More widespread testing for PeV3 would enable us to gain a better understanding of the clinical scope and circulation of this virus.